How Stable Is Labour Market Dualism? Reforms of Employment Protection in Nine European Countries - Werner Eichhorst; Paul Marx (Institute of Labor Economics (IZA), 2019)
Labour market segmentation currently is at the forefront of national and European policy debates. While the European Commission and the OECD try to promote what they see as more inclusive policies, academic observers remain skeptical. Particularly the dualisation literature points to stable political economy equilibria that stack the cards against overcoming divisions between labour market insiders and outsiders. Other contributions point to a more dynamic political setting, in which negative feedback effects tend to challenge any 'dualisation consensus'. Against this background, this paper traces recent reform trajectories in a diverse group of European countries that are characterised by a high share of temporary employment: France, Germany, Italy, Netherlands, Poland, Portugal, Slovenia, Spain, and Sweden. Our case studies show that recent reforms of employment regulation are characterised by much more dynamism than one would expect based on the experiences of the two preceding decades - or based on dualisation or insider-outsider theory. The reform trajectories are characterised by rather contradictory approaches, sometimes in close succession. This even includes, in several cases, substantive deregulation of dismissal protection for open-ended contracts.
Keywords: J41; J42; J65; 330; fixed-term contracts; labour market dualism; segmentation; employment protection; labour market reforms